IMPLEMENTASI PERATURAN TENTANG PENYELENGGARAAN DAN PENGELOLAAN PERPUSTAKAAN UNTUK MENINGKATKAN KESADARAN LITERASI ANAK DI PURWOREJO - Aryani, Novia Dwi; Wahyuni, Sri (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2024)
This study aims to determine and analyse the implementation of Regional Regulation Number 16 of 2017 concerning the Implementation and Management of Libraries to increase children's literacy awareness in Purworejo Regency. In addition, it is also to find out the obstacles faced in implementing Regional Regulation Number 16 of 2017 concerning the Implementation and Management of Libraries to increase children's literacy awareness in Purworejo Regency. This research is an empirical legal research with legislative approach, case approach and conceptual approach. The types of data used in this research are primary data and secondary data. The techniques used in collecting data in this research are literature study and interviews. This research uses a descriptive method, which describes the data obtained through literature study and interviews which are then analysed and a conclusion is drawn. Based on this research, the results show that the implementation of Regional Regulation No. 16/2017 on the Implementation and Management of Libraries to increase children's literacy awareness in Purworejo District has been carried out in accordance with what is stated in this regional regulation. However, the implementation has not been optimal. This can be seen from several aspects that have not been implemented properly. The implementation of Regional Regulation Number 16 of 2017 on the Implementation and Management of Libraries encountered obstacles in managing regional public libraries and obstacles in organising and managing village libraries. There are several solutions offered by the Library and Archives Office to overcome these obstacles.